Chemotaxis and parasitism of the Neotropical fruit fly parasitoid Ganaspis pelleranoi can be altered by pre‐imaginal and imaginal conditioning to fruit volatiles. Issue 5 (23rd March 2022) - Pires, Patricia Daniela da Silva; Sant' Ana, Josué; Redaelli, Luiza Rodrigues; Leite, Natália Alves
Abstract: Search behavior of parasitoids can be triggered by fruit volatiles' perception and modified through pre‐imaginal and/or imaginal conditioning. Ganaspis pelleranoi (Brèthes) (Hymenoptera: Figitidae) is an endoparasitoid of tephritid fruit flies of economic importance. Despite its relevance to agroecosystems, no studies about its learning processes have been done. Therefore, we conducted chemotaxis and parasitism bioassays to evaluate pre‐imaginal and imaginal learning, and memory retention of G. pelleranoi females to volatiles of guava ( Psidium guajava L., Myrtaceae) and apple ( Malus domestica Borkh., Rosaceae). Parasitoids conditioned as immatures were obtained from Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) larvae reared in apple or artificial diet. Parasitoids conditioned as adults were exposed to an apple substrate for 24 or 48 h, and tested after 1, 12, and 24 h. In the olfactometer, parasitoids were given a choice between guava and apple fruits (infested and uninfested). To assess parasitism, three units of parasitism were offered, which consisted of A . fraterculus larvae brushed with water, or with apple or guava pulp. Females preferred guava volatiles regardless of their pre‐imaginal conditioning. When adults were exposed to an apple substrate for 48 h, they preferred volatiles from this fruit for up to 12 h. Females that were conditioned for 24 or 48 h on apple volatiles parasitized more larvae in units with this substrate. Also, the number of flies that emerged from units with apple was lower for females conditioned for 48 h on the same fruit. Therefore, we conclude that pre‐imaginal conditioning in infested fruits was less important than the parasitoid experience to chemicals of fruit volatiles during the adult stage. Also, the longer the exposure of adults to odors, the greater the attraction to those odors and memory retention. Conditioning of G . pelleranoi females could be used as a strategy to improve future biocontrol programs of fruit flies. Abstract : With chemotaxis and parasitism bioassays, we evaluated the difference between pre‐imaginal and imaginal conditioning in learning and memory retention of the native fruit fly parasitoid, Ganaspis pelleranoi (Hymenoptera: Figitidae) females to volatiles of guava and apple. Pre‐imaginal conditioning in infested fruits was less important than parasitoid experience to fruit volatiles during the adult stage. Also, longer exposure of adults to odors led to greater attraction to those odors and memory retention. Hence, parasitoid conditioning may improve fruit fly biocontrol programs.